2013
DOI: 10.1038/mt.2013.148
|View full text |Cite
|
Sign up to set email alerts
|

TP53-independent Function of miR-34a via HDAC1 and p21CIP1/WAF1

Abstract: The tumor suppressor, microRNA-34 (miR-34), a transcriptional target of TP53, functions in a positive feedback loop to activate TP53. Although miR-34 can inhibit cancer cells carrying TP53 mutations, this feedback to TP53 may be a prerequisite for full miR-34 function and may restrict its therapeutic application to patients with intact TP53. To investigate the functional relationships between TP53 and miR-34, and that of other TP53-regulated miRNAs including miR-215/192, we have used a panel of isogenic cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 40 publications
(61 reference statements)
5
41
0
Order By: Relevance
“…miR-34a is often found inactivated in cancer cells (10). It has been reported that inhibition of HDAC1 mimics the miR-34a phenotype (22). In the present study, we have further demonstrated that depletion of HDAC1 upregulated the expression of miR-34a, but had little effect on the expression of miR-34b or miR34c, suggesting that overexpressed HDAC1 exerts its actions on gastric cancer cells by dysregulating miR-34a.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…miR-34a is often found inactivated in cancer cells (10). It has been reported that inhibition of HDAC1 mimics the miR-34a phenotype (22). In the present study, we have further demonstrated that depletion of HDAC1 upregulated the expression of miR-34a, but had little effect on the expression of miR-34b or miR34c, suggesting that overexpressed HDAC1 exerts its actions on gastric cancer cells by dysregulating miR-34a.…”
Section: Discussionsupporting
confidence: 73%
“…In accordance, in the present study we have shown that depletion of HDAC1 by siRNA resulted in an altered expression of 101 differentially expressed miRNAs matching the 4-fold threshold in gastric cancer cells. miR-34, a transcriptional target of p53, is a potent tumor suppressor that inhibits a broad range of cancer cells by repressing a plethora of oncogenes that control cell proliferation, senescence, apoptosis and metastasis (10,22). The miR-34 family comprises three processed miRNAs that are encoded by two different genes: miR-34a is encoded by its own transcript, whereas miR-34b and miR-34c share a common primary transcript (10).…”
Section: Discussionmentioning
confidence: 99%
“…To gain additional evidence for an indirect mechanism of HbF regulation by miR-34a, we analyzed proteins known to be negative regulators of g-globin transcription and previously shown to be silenced by miR-34a including YY1, HDAC1, and STAT3. [32][33][34][35][36] YY1 binds the À1086 region in the upstream g-globin promoter to silence gene expression 55 ; by contrast, HDAC1 and HDAC2 are protein components of the nucleosome remodeling deacetylation complex 56 which plays a pivotal role in DNA methylation associated with globin silencing in b-YAC mice. 57 Histone deacetylase inhibitors such as sodium butyrate induce HbF 58 by inhibiting HDACs broadly producing histone hyperacetylation and a favorable open chromatin conformation to facilitate gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of genes are targeted by miR-34a, 27,[30][31][32][33][34][35][36] including the known g-globin repressors YY1, HDAC1, and STAT3 among others. Therefore, we performed studies to determine whether miR34a indirectly regulates g-globin expression through one of these negative regulators.…”
Section: Mir34a Overexpression Silences Stat3 Gene Expressionmentioning
confidence: 99%
“…Silencing of HDAC expression induces a G2/M growth arrest and stimulates p21 promoter activity in colon cancer cells (35). Although the cell cycle-dependent kinase inhibitor p21 is known to be transcriptionally regulated by p53, induction of p21 by HDAC inhibitors does not always require the presence of wild-type p53 (36). Both p53-dependent and p53-independent anticancer effects have also been demonstrated for HDAC inhibitors (37).…”
Section: Minmentioning
confidence: 99%